College Students' Perceptions of the Links Between Alcohol Use and Sexual Experiences. (August 2016) - Lefkowitz, Eva S.; Waterman, Emily A.; Morgan, Nicole R.; Maggs, Jennifer L.
Alcohol use is associated with impaired decision making and unwanted sexual outcomes, but emerging adults generally perceive the co-occurrence of alcohol use and sexual behavior positively. The current study examined perceived links between alcohol use and sexual experiences. Data were from 279 college students using stratified random sampling with replacement (56% female, 25% Hispanic/Latino, 22% African American, 28% Asian American/Pacific Islander, and 51% European American; M = 19.95 [0.43] years old). We coded participants' responses to an open-ended question about how their alcohol use and sexual feelings were related. Students generally perceived that alcohol is facilitative of sex or has no effect. The most common responses were that alcohol leads to arousal and disinhibition. Almost no students mentioned alcohol's impact on contraceptive use or sexual assault. Results differed by gender, prior sexual behavior, and heavy drinking. We interpret results in light of alcohol myopia theory and discuss implications for prevention.